Compression pressurized direct fuel injection to reduce emissions from existing small two-stroke transports - Gitano-Briggs, Horizon Walker, author; Willson, Bryan, advisor; Levinger, Nancy E., committee member; Mitchell, Charles E., committee member (Colorado State University. Libraries, 2004)
The two-stroke engines commonly used in transports in developing countries suffer from exceedingly high emissions of hydrocarbons (HC) and carbon monoxide (CO). The problem of emissions from two-stroke engines will be largely addressed via emissions regulations on new vehicles typically resulting in their replacement with four-stroke engines. The existing fleet of two-stroke vehicles, however, is liable to be a major source of air pollution for the next few decades. Technologies, such as direct fuel injection (DI) and catalytic after-treatments, exist which are capable of being retrofitted to existing two-stroke engines to resolve their emissions problems. However, they are generally prohibitively expensive for applications in developing countries. A review of existing technologies indicates that direct fuel injection is the most promising and mature technology readily applicable to existing two-stroke machines. A cost reduced design modification using compression pressurization of an Air Blast DI (ABDI) system is proposed and modeled. A compression pressurized DI engine retrofit is designed and fabricated. Finally, emissions and power output measurements are taken on the compression pressurized direct fuel injection system showing similar power production to the carbureted engine, an 86% reduction in HC emissions, and an 83% reduction in CO at a cost of approximately two thirds of the ABDI system.
Keywords: mechanical engineering; automotive materials; transportation; automotive engineering